Environmental approach for securing Halalan Toyyiban concept in food safety- a mini review - Ahmad, Farah Najwa; Nordin, Noor Faizul Hadry (International Institute for Halal Research and Training (INHART), International Islamic University Malaysia, 2023)
The relationship between Halalan Toyyiban concept and food safety is well known and discussed among the scholars since the early years. Muslims are guided by the concept that is highlighted in the Quran to consume food. However, the widely occurred environmental pollution and contamination around the globe had threatened the status of the natural food resources. One of the major threats to global food safety is chemical contamination from environment. By harnessing the ability of the microorganism in the environment to restore the nature is one of the approaches used to ensure the concept of toyyiban is safely fulfilled. Using the Qur’an as primary sources and other published articles, this article connects the links between the wider halalan toyyiban concept and the environmental sciences related approaches and subsequently provides alternative perspective to the halalan toyyiban concept especially for the food safety issues.